How to apologize - LaRochelle, David (Candlewick Press, 2021)
From the team behind See the Cat: Three Stories About a Dog comes a funny and handy guide that explains just how (and how not!) to say I'm sorry. Wouldn't the world be a better place if everyone knew how to apologize? Luckily, this humorous guidebook is full of practical tips about when, why, and how to say you're sorry. From a porcupine who accidentally popped his friend's balloon to a snail who was running so fast he stepped on a sloth's toes, hilarious examples and sweet illustrations abound. For both listeners who are just learning and older readers who need a refresher, this book will come as a welcome reminder that even though apologizing can be hard, it doesn't have to be complicated.